Patellar Tendon Tenotomy for Treatment of Patella Baja and Extension Deficiency - Kennedy, Mitchell I. (Arthrosc Tech, 2019)
Extension loss due to patella baja is a rare but devastating postoperative complication associated with knee surgery. The most common causes of patella baja are prolonged postoperative immobilization, over-distalization of the patellar tendon during patella-related surgical procedures (i.e., tibial tubercle osteotomy and patellar tendon reconstruction), and inadequate knee range-of-motion exercises postoperatively. Patella baja can cause significant functional limitations owing to knee-related stiffness, pain, and weakness. Arthroscopy with scar tissue debridement is the standard of care for patients with arthrofibrosis in whom conservative treatment has failed. However, when this surgical approach fails, patients with continued patella baja may be candidates for open patellar tendon tenotomy as a salvage procedure.